DYNAMICS OF TRADEMARK LAW: A REVIEW OF THE CASE OF INTER IKEA SYSTEM B.V. VS. PT RATANIA KHATULISTIWA IN DECISION NO. 264 K/PDT.SUS-HKI/2015 - Pambudi, Amanda Devina Cellia; Prastyanti, Rina Arum (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Trademark can be interpreted as a naming or thing that can be used as a mention in a product. Trademark is included in one of the scope of Intellectual Property Rights. Intellectual Property Rights that can provide protection and legal certainty against a trademark. Without legal protection, the trademark will be very easy to imitate so as to cause harm to one party. This research focuses on the decision of the Supreme Court No. 264 K/Pdt.Sus-HKI/2015 which filed a trademark dispute between Inter IKEA System B.V. and PT Ratania Khatulistiwa. The two parties involved are the owner of the IKEA brand and the applicant for the IKEA brand. The purpose of this study is to analyze the judge's decision and the elements contained therein as well as outline the lawsuit application filed by the plaintiff. This research is made using the normative juridical method with secondary materials as the main material used. In the case between PT Ratania Khatulistiwa against Inter IKEA System B.V. both seek the brand "IKEA" as the brand they want to have.